Concepts and Methods for the Study of Chinese Religions, Volume II, Intellectual History of Key Concepts - Scott, Gregory Adam; Travagnin, Stefania (De Gruyter, 2020)
The three-volume project 'Concepts and Methods for the Study of Chinese Religions' is a timely review of the history of the study of Chinese religions, reconsiders the present state of analytical and methodological theories, and initiates a new chapter in the methodology of the field itself. The three volumes raise interdisciplinary and cross-tradition debates, and engage methodologies for the study of East Asian religions with Western voices in an active and constructive manner. Within the overall project, this volume addresses the intellectual history and formation of critical concepts that are foundational to the Chinese religious landscape. These concepts include lineage, scripture, education, discipline, religion, science and scientism, sustainability, law and rites, and the religious sphere. With these topics and approaches, this volume serves as a reference for graduate students and scholars interested in Chinese religions, the modern cultural and intellectual history of China (including mainland China, Taiwan, Hong Kong, and Chinese communities overseas), intellectual and material history, and the global academic discourse of critical concepts in the study of religions
Description based on online resource; title from PDF title page (publisher's Web site, viewed 05. Mai 2020)
Keywords: China; Chinese intellectual history; Chinese material culture; Chinese religions; Leitbegriffe; Religion; academic study of religion; LITERARY CRITICISM / Asian / General; Religion -- Methodology -- Congresses; Religion -- Research -- Congresses; Theology -- Research -- Congresses; Aufsatzsammlung